(untitled) (Research, Society and Development, 2022)
Homeschooling is a method of education in which the child or adolescent is supervised by their family members in their homes, providing personalized education based on values ​​that the family believes are most appropriate. The present work will approach the subject analyzing the understanding of General Repercussion of the STF 822 and how it could be introduced in the Brazilian legal system, allowing its application. The difficulties on the subject are that in Brazil there is no law regulating this practice, thus not being allowed such a teaching method in the country. The study of the subject is of great importance since more and more cases of bullying increases, harming several children and leading them to even think about giving up on life, with home schooling being an alternative teaching for these and other diverse cases in which the parents do not condone school education. Among the difficulties pointed out, this work aims to explain the current impasse of regulation and clear doubts from interested families. The methodological procedures used to form this work were done through bibliographic research, with a deductive approach, with a well-defined objective. Therefore, it is concluded that the issue needs regulation in order for it to begin to take effect. Bill 3,179 of 2012 is on the way to being approved and regulating the subject, since the General Theme 822 of the STF embraced the thesis that there is public subjective right conferred by the Constitution on the subject, but its application is not possible due to the lack of regulation.